Pathobiochemistry of arthrofibrotic remodeling. Issue 4 (27th April 2017) - Faust, Isabel; Traut, Philipp; Knappe, Cornelius; Hendig, Doris
Aims and Objectives: Arthrofibrosis is defined as painful impairment of joint flexibility due to fibrotic tissue remodeling after joint trauma or surgery. The incidence of arthrofibrosis after knee replacement surgery is 5 to 10%. Although conventional therapeutic approaches as for instance mobilization and physiotherapy are applied, an effective and causative therapeutic regimen is not known. Materials and Methods: To characterize arthrofibrotic remodeling of the extracellular matrix, to develop new therapeutic approaches and to define diagnostic biomarkers and therapeutic targets, understanding of biochemical principles is urgently required. Fibrotic remodeling was described in several tissues, whereas synovial fibrosis is one of the least investigated fibrotic disorders. Nevertheless, molecular key events in fibrosis seem to be the same and are initiated by exogenic or endogenic tissue damage and differentiation of resident fibroblasts of the connective tissue to myofibroblasts. Known inductors of myofibroblast differentiation are fibrotic growth factors, which are secreted by platelets, damaged tissue and inflammatory cells, as well as mechanical strain. Research studies concerning cardiac fibrosis in tako-tsubo cardiomyopathy also define emotional stress and sympathicotonic destabilization as profibrotic stressors. Myofibroblasts generate contractile forces and synthesize extracellular matrix components, so that scar tissue accumulates. While myofibroblasts disappear by apoptosis in physiological wound healing, they persist in fibrosis. Results: Recently, we could demonstrate that increased expression of human xylosyltransferase (XT)-I, an enzyme which catalyzes the rate limiting step in proteoglycan glycosylation, is linked to abnormal extracellular matrix remodeling. Serum XT activity reflects proteoglycan synthesis rate and is known as fibrosis biomarker in liver fibrosis or scleroderma. Our data also indicate that XT-I is a cellular key mediator of arthrofibrosis. However, we suggest that molecular changes based on arthrofibrosis are, due to local restriction of the affected joint by the blood-synovial-barrier, not detectable in human serum. Currently, we study synovial XT activity of arthrofibrosis patients and controls in a multicenter study. Conclusion: In summary, we give insights into the complex pathobiochemistry of arthrofibrosis as well as current research projects. A deeper characterization of the involved mechanisms might not only contribute to control and inhibit fibrotic remodeling by interfering with components of fibrotic signal cascades but also to establish new therapeutic strategies.